2009
DOI: 10.1590/s1516-35982009000900026
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação do uso de frações indigestíveis do alimento como indicadores internos de digestibilidade em ovinos

Abstract: RESUMO -Avaliou-se o uso de matéria seca indigestível (MSi) e de fibra detergente neutro indigestível (FDNi) como indicadores internos de digestibilidade em ovinos. Utilizaram-se dados e amostras provenientes de seis ensaios independentes de digestibilidade com ovinos mantidos em gaiolas de metabolismo recebendo à vontade diversos tipos de volumoso e/ou concentrado. Os resíduos indigestíveis (MSi e FDNi) foram determinados após 144 horas de incubação in situ de amostras de alimentos e fezes. O grau de recupera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
9

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 11 publications
1
8
0
9
Order By: Relevance
“…However, in another study on lambs, Kozloski et al (2009) observed that fecal recovery of internal indigestible DM and iNDF markers was not complete and varied considerably among assays. These authors suggest that digestion and/or partial absorption of the markers is a probable cause for this variation, along with physicochemical modifications throughout the digestive tract and deficiencies in analytical procedures.…”
Section: Discussionmentioning
confidence: 95%
“…However, in another study on lambs, Kozloski et al (2009) observed that fecal recovery of internal indigestible DM and iNDF markers was not complete and varied considerably among assays. These authors suggest that digestion and/or partial absorption of the markers is a probable cause for this variation, along with physicochemical modifications throughout the digestive tract and deficiencies in analytical procedures.…”
Section: Discussionmentioning
confidence: 95%
“…The fecal recovery of the external markers was below 100% is attributed to the partial absorption of the marker in the digestive tract or to its transformation into other compounds, which may cause an underestimate of the total fecal DM production. The fecal recovery of iDM was the one that was closest to 100%, which was obtained with total feces collection and was higher than that obtained by Kozloski et al (2009). The use of iDM as a marker can provide exact results and high correlations with the total collection, never the less, the presence of contaminants may compromise the obtained results, since no detergent solutions are used to obtain the iDM content, which prevents the removal of residues from the cell wall and bacterial contamination.…”
Section: Resultsmentioning
confidence: 83%
“…Detmann et al (2007) evaluated internal markers iDM, iNDF, and iADF in grazing cattle and found better estimates with iDM and iNDF for indirect evaluation of digestibility, whereas the values obtained by iADF showed variable effects with errors stemming from the analytical process, which affected its accuracy as a marker. Kozloski et al (2009) observed a fecal recovery of iDM of 108.5%, and no differences between the digestibility of organic matter estimated by that marker (77.0%) and by total collection (76.00%); however, these authors stress the little precision and variation in the estimate when changes are caused by experimental treatments. Regarding the external markers, the fecal recovery of Cr 2 O 3 (92.5±6.6%) was higher, near 100%, result similar to the 86.1 obtained by Rodrigues et al (2010) in sheep also fed highconcentrate diets.…”
Section: Resultsmentioning
confidence: 85%
“…The apparent digestibility (AD) of the DM, CP, NDF, ADF and energy, were calculated from the difference between ingested nutrients and nutrients excreted in the faeces, as a function of nutrient intake (KOZLOSKI et al, 2009): AD (% ) = [ (nutrient intakenutrient excreted in the faeces) / nutrient intake ] x 100. The metabolisable energy (ME) was obtained by subtracting the energy losses through the urine and methane, from the digestible energy.…”
Section: Th28dmentioning
confidence: 99%